Makna Syukur dalam Musik Video Yura Yunita di Youtube - Ranti Fazrin; Alex Sobur (Bandung Conference Series: Communication Management, 2023)
Abstract. The research entitled The Meaning of Gratitude in Yura Yunita's Music Video on Youtube is motivated by how the signs presented as gratitude through music videos are currently in demand by a wide audience. Music videos are a medium for musicians to convey meaningful messages to their listeners. This study aims to determine the meaning of gratitude in the music video “Dunia Tipu-Tipu” through John Fiske's semiotic theory and approach. The research method used is qualitative. Observation and Documentation as data collection techniques in this study as well as data analysis techniques in terms of the level of reality, the level of representation and the level of ideology. The results of the study show that the meaning of gratitude in the music video "Dunia Tipu-Tipu" is seen from the level of reality through the code of gestures, clothing, appearance, expression and sound. describes the presence of the closest people such as parents, partners and friends who are always there under any circumstances and conditions. Then at the representation level through the camera code, music, lighting and sentences show the meaning of gratitude in form of attention by paying attention to each other’s condition, warm hugs and holding hands. And at the ideology level, it can be concluded that the music video for "Dunia Tipu-Tipu" has an ideology of being grateful for the feelings you have for those closest to you. Abstrak. Penelitian yang berjudul Makna Syukur dalam Musik Video Yura Yunita di Youtube ini dilatarbelakangi oleh bagaimana tanda-tanda dihadirkan sebagai rasa syukur melalui musik video yang sedang diminati saat ini oleh khalayak luas. Musik video menjadi salah satu media bagi musisi untuk menyampaikan pesan yang memiliki makna kepada para pendengarnya. Penelitian ini bertujuan untuk mengetahui bagaimana makna syukur pada musik video “Dunia Tipu-Tipu” melalui pendekatan teori semiotika John Fiske ditinjau dari dari level realitas, level representasi dan level ideologi. Metode penelitian yang digunakan yaitu kualitatif. Observasi dan Dokumentasi sebagai teknik pengumpulan data pada penelitian ini. Hasil penelitian menunjukkan makna syukur pada musik video “Dunia Tipu-Tipu” ditinjau dari level realitas melalui kode gesture, pakaian, tampilan, ekspresi dan suara. Digambarkannya atas kehadiran orang-orang terdekat seperti orang tua, pasangan dan sahabat yang selalu ada dalam keadaan dan kondisi apapun. Lalu pada level representasi melalui kode kamera, music, lighting dan kalimat ditunjukkannya makna syukur dalam bentuk perhatian dengan memperhatikan kondisi satu sama lain, pelukan hangat dan genggaman tangan. Dan dalam level ideologi dapat disimpulkan bahwa musik video “Dunia Tipu-Tipu” memiliki ideologi bersyukur atas rasa yang dimiliki terhadap orang-orang terdekat.